Not Only a Host Country... - Myrotis, Panagiotis (HAPSc Policy Briefs Series, 2024)
During the period of the economic crisis of 2010-2019, Greece, in addition to county’s economic dimension, had to face the flight of its human capital abroad. The conditions created by the crisis resulted in the Brain Drain phenomenon making its appearance in the European country. The peculiarity of this type of immigration is that the country suffers, economically and socially to a large extent, due to the absence of the human capital on which it has invested. The structure of the study is based on the analysis of primary and secondary sources with a productive process. First, a literature overview of the term Brain Drain is made, then the findings are correlated with the Greek case and the role that the diaspora Greeks can play in Greece after the crisis. Finally, in this paper there is an attempt to develop policy proposals aimed at their repatriation.